THE ACTIVITY OF TRANSPOSING DIRECTIVE 2014/94/EU OF THE EUROPEAN PARLIAMENT AND COUNCIL OF 22 OCTOBER 2014 ON THE DEPLOYMENT OF ALTERNATIVE FUELS INFRASTRUCTURE. THE POST-TRANSPOSING ATTRIBUTIONS OF THE ROMANIAN ENERGY REGULATORY AUTHORITY - Ionela-Alina ZORZOANĂ (Challenges of the Knowledge Society)
This article proposes an analysis of the activity of transposing the Directives, an obligation of the Member States of the European Union provided by the Treaty on the Functioning of the European Union. The transposing obligation entails that the Member State to which a Directive is addressed has the option to choose the form and means and the important issue is that the obtained result should be the one set up by the concerned Directive. Following up the study, we shall analyze the sanctions that can be implemented by the European Commission in case of failure of transposing or partially transposing a Directive. We further proposed ourselves to analyze the case of Directive no. 2014/94/EU of the European Parliament and Council from 22 October 2014 on the deployment of alternative fuels infrastructure. The analysis shall refer to the scope of issuing the Community deed, but especially to the challenges recorded during the process of transposing Directive 2014/94/EU in Romania and the triggering of the infringement procedure against Romania. The article shall also compare the stage of transposing the Directive in other Member States. Last, but not least, we shall also make an analysis of the attributions of the Romanian Energy Regulatory Authority in domestic law.